The Biophysical Modelling of the Human Aging - Vincze, Janos; Vincze-Tiszay, Gabriella (British Journal of Healthcare and Medical Research, 2023)
The role of the biophysics consists of the study of the vital processes which take place in the living organisms, their correlations in the discovery of the causal relationships between the phenomena, establishing the underlying connections and the quality differences of the processes which take place in the living organism. In the contemporary times of explosive development of nature sciences, medical biophysics – a borderline science with interdisciplinary aspects – having as object the modelling of the human organism, becomes a basic discipline in the biomedical studies. Medical biophysics can be applied in all the fields of medicine. The problem of aging preoccupied the researchers a lot. Several theories and hypothesis have been issued regarding the causes of aging. The aging itself are an indispensable condition of the evolution of life on earth. The aging is characteristics of the all analyzers. In older age, the perception of posture becomes less steady and precise, because structural changes occur in the spinal column that clearly mislead our organ sensing balance, from the aspect of information. They found that the so-called method of amplitude estimation resulted in values with very dispersed intervals, therefore, they applied the correlation of the analyzers.